Histopathological growth pattern of liver metastases as an independent marker of metastatic behavior in different primary cancers - Bohlok, Ali; Richard, François; Lucidi, Valerio; Asmar, Antoine El; Demetter, Pieter; Craciun, Ligia; Larsimont, Denis; Hendlisz, Alain; Van Laethem, Jean Luc; Dirix, Luc; Desmedt, Christine; Vermeulen, Peter; et al. (Frontiers in Oncology, 2023)
Surgical resection can lead to prolonged survival in patients with isolated liver metastases (LM) from various primary cancers. However, there are currently no validated predictive markers to discriminate between these oligo/argometastatic patients, who will benefit from surgery, and those with diffuse metastatic behavior in whom surgery will be futile. To evaluate whether the tumor microenvironment, or histopathological growth pattern (HGP), of LM reflects the type of metastatic progression independently of the origin of the primary cancer, we analyzed a combined series of patients who underwent surgery for colorectal LM (N=263) or non-colorectal LM (N=66). HGPs of LM were scored in each patient to distinguish between desmoplastic HGP (all LM showing a complete encapsulated pattern) and non-desmoplastic HGP (at least one LM with some infiltratingreplacement component). In the entire series, 5-year overall and progression-free survival were, 44.5% and 15.5%, respectively, with no significant differences between colorectal and non-colorectal LM. In patients with desmoplastic HGP, 5-year overall and progression-free survival were 57% and 32%, respectively, as compared to 41% and 12%, respectively, in patients with non-desmoplastic-HGP (p=0.03 and 0.005). Irrespective of cancer origin and compared to traditional risk factors, desmoplastic HGP was the most significant predictor for better post-operative overall survival (adjusted HR: 0.62; 95% CI: [0.49-0.97]; p=0.035) and progression-free survival (adjusted HR: 0.61; 95% CI: [0.42-0.87], p=0.006). This suggests that the HGP of LM may represent an accurate marker that reflects the mode of metastatic behavior, independently of primary cancer type.